SUPERVISION AND ENFORCEMENT OF LABOR SANCTIONS AGAINST VIOLATIONS OF PERMITS TO USE FOREIGN WORKERS IN THE PROVINCE OF SOUTH SULAWESI - Wawan Haryanto; Fitriani Jamaluddin; Rizka Amelia Armin (Constitutional Law Society, 2022)
The importance of supervising foreign workers working in Indonesia needs to be controlled and supervised by the Ministry of Manpower. Uncontrolled use of foreign workers will have an impact on domestic workers. Therefore, the use of foreign workers must meet the provisions of positions that may be occupied by foreign workers, so that for positions that can still be carried out by Indonesian workers, domestic workers should be prioritized. The research used in this research is social law research/empirical research which is carried out with an approach to the legal reality in society. Related to employment crimes, it is a judicial repressive measure as the last step in enforcing labor law. From the law enforcement process in the field of labor inspection, we know that the law enforcement process is carried out in three stages, namely, the stage of development, supervision and enforcement of sanctions.